Analytical determination of nicotine and related compounds and their metabolites - Gorrod, J. W. (John W.); Jacob, Peyton; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1999)
This book provides for the first time a single comprehensive source of information on the analytical chemistry of nicotine and related alkaloids. The editors have brought together scientists from academia and the tobacco industry to describe the state-of-the-art of the chemistry and analytical methods for measurement of nicotine. Both the scope and detail of the book are impressive. Chapters describe the history, pharmacology and toxicology of nicotine, the biosynthesis of nicotine and other alkaloids in the tobacco plant, the general chemistry of nicotine and the analytical methodologies that have been used to measure nicotine and related alkaloids in biological specimens, in tobacco and pharmaceutical products and in tobacco smoke. There is also a comprehensive review of the chemistry and toxicology of nicotine-derived nitrosamines, an important class of tobacco carcinogens.
Chapter headings: Foreword. List of Contributors. -- Pharmacological Significance of Nicotine. -- Biosynthesis of Nicotine and Related Compounds. Biotransformation of Nicotine and Related Tobacco Alkaloids in Mammalian Systems. Chemical Properties of Nicotine and Other Tobacco-Related Compounds. The Physical Chemistry of Nicotine. Use of Gas Chromatographic and Mass Spectrometric Techniques for the Determination of Nicotine and its Metabolites. Use of High-Performance Liquid Chromatographic-Mass Spectrometric (LC-MS) Techniques for the Determination of Nicotine and its Metabolites. Use of Immunoassay Techniques for the Determination of Nicotine and its Metabolites. Determination of Nicotine in Tobacco, Tobacco Processing Environments and Tobacco Products. Determination of Nicotine in Pharmaceutical Products and Dietary Sources. Nitrosamines Derived from Nicotine and Other Tobacco Alkaloids. Determination of Nicotine in Mainstream and Sidestream Cigarette Smoke. Nicotine in Environmental Tobacco Smoke. Determination of Nicotine and its Metabolites in Biological Fluids: in vivo Studies. Determination of Nicotine and its Metabolites in Biological Fluids: in vitro Studies. Uses and Abuses of Cotinine as a Marker of Tobacco Smoke Exposure.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Nicotine -- Analysis; Nicotine -- Metabolism; Nicotine -- Analyse; Nicotine -- Métabolisme.; MEDICAL -- Pain Medicine; MEDICAL -- Psychiatry -- Psychopharmacology; Nicotine -- Analysis; Nicotine -- Metabolism; Droga vegetal; Nicotine -- analysis; Nicotine -- metabolism; Electronic books